Greenhouse gas emissions of rice straw return varies with return depth and soil type in paddy systems of Northeast China. Issue 12 (15th October 2021) - Zhang, Hao; Liang, Shuang; Wang, Yuehong; Liu, Siwen; Sun, Hongda
ABSTRACT: A two-year field experiment was performed to investigate greenhouse gas emissions from rice straw return to different return depths and soil types. The experiment comprised of six treatments: without straw return (silty clay loam, SC; sandy loam, SL); straw return to topsoil (SCT, SLT); and straw return to subsoil (SCS, SLS). SCT and SLT released 2402.18 and 2494.01 kg ha −1 more CO2 than SC and SL in total, respectively. Straw return to topsoil and subsoil in both soil textures significantly increased CH4 emissions. Compared to the total cumulative CH4 fluxes in SC and SL, those of SCT and SLT increased by 239.62 and 131.34 kg ha −1, and those of SCS and SLS increased by 125.07 and 89.93 kg ha −1, respectively. SCT and SCS emitted 389.06 and 168.94 g ha −1 less N2 O than SC in total, respectively. SL released 146.28 and 72.06 g ha −1 more N2 O than SLT and SLS in total, respectively. The variations in the ratio of the total cumulative fluxes of CO2 and CH4, indicate that rice straw return to silty clay loam and subsoil tend to release more carbon in the form of CH4 compared to sandy loam and topsoil, respectively.